Actions Ultra Vires Minister of State-Owned Enterprises in the Procurement of Goods and Services at Subsidiaries of State-Owned Enterprises - Prasetya, Fauzan; Azheri, Busyra; Ismansyah; Husin, Sukanda (International Journal of Scientific Research and Management (IJSRM), 2020)
The Government through the Minister of State-Owned Enterprises (SOEs) in his position as a Shareholder in SOEs (Indonesian: Badan Usaha Milik Negara (BUMN) enacts the Minister of SOE Regulation Number: PER-15 / MBU / 2012 Regarding Amendments to the Regulation of the State Minister of State-Owned Enterprises Number PER-05 / MBU / 2008 Regarding Guidelines General Implementation of Procurement of Goods and Services of State-Owned Enterprises in SOE Subsidiaries. Which actions have raised the pros and cons of the capacity of the Minister of SOEs as BUMN shareholders in SOE subsidiaries. The legal status of BUMN subsidiaries in the BUMN holding scheme remains a separate legal entity that has their respective organs and responsibilities as regulated in the Law of PT. When the SOE Minister acts on behalf of the State, he is the shareholder of SOE as contained in Article 1 paragraph (1) of the BUMN Law. As a shareholder, the Minister of SOEs can only establish policies towards SOEs. Whereas in SOE Subsidiaries, the shareholders are SOEs as legal subjects. So that the provisions of Article 1 number (2) SOE Ministerial Regulation Number 3 of 2012 whereby the Minister of BUMN cannot act as a shareholder. The enactment of BUMN Permen 15/2012 to SOE Subsidiaries by SOEs Minister in his capacity as BUMN shareholder is an ultra vires action.